A new genus of minute ammobatine bees (Hymenoptera: Apidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2006)
A new genus of minute ammobatine bees is described and figured. Chiasmognathus gen. n. (Apidae: Nomadinae: Ammobatini) consists of three previously described species; Chiasmognathus gussakovskii (Popov) comb. n., C. orientanus (Warncke) comb. n. (with Pasites orientanus cyprius Warncke as a new synonym), and C. aegyptiacus (Warncke) comb. n.; as well as three or four additional species to be described in a forthcoming contribution. The genus occurs in eastern Europe, the Levant, and central, southwestern, and southern Asia. Chiasmognathus are cleptoparasites of species of Nomioides (Halictidae: Halictinae: Nomioidini).
Keywords: Azija; čebele; entomologija; favna